2016
DOI: 10.1159/000445294
|View full text |Cite
|
Sign up to set email alerts
|

The Possibly Reversible Isotretinoin Effect of Decreased Ovarian Reserve in Sprague-Dawley Albinos: Part I, Biochemical Analyses

Abstract: Background: The study aims to determine the detrimental effects of 7.5 mg/kg/day isotretinoin treatment on the anti-Mullerian hormone (AMH) levels in an experimental study to see whether the effects on ovarian reserve are reversible. Methods: Blood was sampled in 16 Sprague-Dawley albinos before any treatment to see baseline AMH levels. Then, the rats were randomly divided into 2 groups. Control group received only 1.0 ml soybean oil per oral for 30 days, whereas the study group received 7.5 mg/kg/day isotreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Furthermore, no statistically significant changes in AMH values 1 month after the last dose of isotretinoin relative to pretreatment values were found. These results indicate that after isotretinoin cessation, AMH concentrations increased, providing additional evidence for the first time in the literature, suggesting that the impact of isotretinoin on ovarian reserves could be reversible [13].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, no statistically significant changes in AMH values 1 month after the last dose of isotretinoin relative to pretreatment values were found. These results indicate that after isotretinoin cessation, AMH concentrations increased, providing additional evidence for the first time in the literature, suggesting that the impact of isotretinoin on ovarian reserves could be reversible [13].…”
Section: Discussionsupporting
confidence: 69%
“…In contrast to previous research, Korkmaz et al [13] tested AMH values prior to drug administration, as well as AMH values immediately after and one month after the last dose of isotretinoin administration, to see whether there was any drug impact and how long it lasted. While there were no major differences between the groups, the isotretinoin treatment group's AMH values were slightly lower on the day immediately following the last dose (p = 0.02) than the pretreatment values.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, several clinical studies investigating the effects of isotretinoin on female fertility have been reported to reduce ovarian reserves [10-12]. Similar data have been reported in animal studies in which rats were treated with 7.5 and 15 mg/kg/day isotretinoin [13, 14]. However, these studies investigating the toxic effects of isotretinoin on reproductive organs are few [15, 16].…”
Section: Introductionmentioning
confidence: 82%
“…In a clinical study, it has been reported that systemic treatment with isotretinoin has no long-term side effects on fertility in humans [28]. However, in an animal study, the reversible effect of isotretinoin on the ovaries was examined [14]. In this study, basal AMH levels of blood samples of 16 Sprague-Dawley albinos were measured before isotretinoin administration, and then rats were randomly divided into 2 groups: 0 mg/kg/day (group 1) and 7.5 mg/kg/day (group 2).…”
Section: Discussionmentioning
confidence: 99%